The Adjacency Pair Patterns in Spoken Interaction of Roundtable Discussion With Susi Pudjiastuti - Iswara, Jati Widya; Rukmini, Dwi; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2019)
Conversation Analysis (CA) is an issue of Pragmatics. CA is a way to analyze a conversation by its elements such as turn-taking, and adjacency pair produced by the speakers. In this present study, the researcher conduct research in the field of CA, but more specific the researcher investigates in the adjacency pair patterns and communicative functions in spoken interaction of roundtable discussion with Susi Pudjiastuti. Since people know that Minister Susi has a lot of controversy on her duty as an Indonesia Minister of Maritime affairs and Fisheries, there are such unique facts that can be seen by this present study. The aims of this research are to investigate how do the adjacency pair patterns constructn the spoken interaction of roundtable discussion with Susi Pudjiastuti, how the communicative functions realized in the roundtable discussion, and how do the power and status relation reflect to the participants of roundtable discussion. Qualitative method used in this present study. The researcher found eleven patterns of adjacency pair that construct in the rountable discussion. Then, eleven communicative functions were realized in the roundtable discussion. At last, the researcher found many interruption produced by Minister Susi, and it shown that power and status relation reflect to the way she is more dominated in the roundtable discussion. This research has beneficial value for teacher, lecturer, and student in order to enrich their knowledge especially in adjacency pair patterns.